Pengaruh Tingkat Pendidikan dan Keaktifan Organisasi Tentang Antusiasme Berwirausaha di Kalangan Mahasiswa Pendidikan Ekonomi Angkatan 2020-2021 Uniwara - Fahri Wardhana; Sugeng Pradikto (Journal of Creative Student Research, 2025)
This study aims to analyze the impact of education level and organizational participation on Economic Education students' interest in entrepreneurship at PGRI Wiranegara University (UNIWARA) class of 2021-2022. The methodology applied in this research is a quantitative approach using a survey. Information was obtained through questionnaires administered to students and analyzed using statistical methods. Research findings indicate that education plays an important role in influencing interest in entrepreneurship, where formal education provides the knowledge and skills needed for entrepreneurship. Apart from that, participation in organizations also has a good impact on interest in entrepreneurship, because it provides practical experience and opportunities to network. The combination of these two factors shows a more significant impact than if you only pay attention to one factor alone. It is hoped that the results of this research can contribute to the development of the entrepreneurship education curriculum and extracurricular activities to increase students' interest in entrepreneurship.